Saturated output of a Ge XXIII x-ray laser at 19.6 nm - Zhang, J; Warwick, P; Wolfrum, E; Key, M; Danson, C; Demir, A; Healy, S; Kalantar, D; Kim, N; Lewis, C; Lin, J; MacPhee, A; et al. (1996)
We report on measurements of the saturated single frequency output of a Ge XXIII x-ray laser on the J=0→1 transition at 19.6 nm from a refraction compensating double target driven by 150 J of energy from 75-ps Nd-glass laser pulses. The 19.6-nm line completely dominated the laser output. The output energy was measured to be 0.9 mJ in a beam of 6.6×30 mrad2 divergence, corresponding to a conversion efficiency of 6 ×10-6.